2016
DOI: 10.1111/ejn.13390
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine D3 receptor, a quarter century later

Abstract: This review updates the existing knowledge suggesting a role for the D3 receptor in schizophrenia and drug addiction. The D3 receptor is expressed in brain regions controlling reward, emotions, and motivation. Antipsychotics bind in vitro to the D3 receptor with similar affinity as to the D2 receptor, and occupancy of D3 receptors in vivo by these compounds given acutely at clinical dosage have been demonstrated in Positron Emission Tomography (PET) studies. The D3 receptor modulates glutamatergic pathways fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 220 publications
4
164
1
4
Order By: Relevance
“…Indeed, patients diagnosed with PTSD are significantly more likely to abuse drugs and become addicts (Kessler et al, ; Pietrzak, Goldstein, Southwick, & Grant, ; Seal et al, ). There are considerable data indicating that highly selective DA D 3 receptor antagonists are efficacious in decreasing the appetitive and reinforcing actions of cocaine, methamphetamine, nicotine, heroin and ethanol in rats (Heidbreder & Newman, ; Heidbreder et al, ; Sokoloff & Le Foll, ). Thus, if these results can be translated to humans, they suggest that highly selective DA D 3 receptor antagonists may be efficacious in attenuating PTSD symptoms, while simultaneously decreasing the likelihood of drug abuse and addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, patients diagnosed with PTSD are significantly more likely to abuse drugs and become addicts (Kessler et al, ; Pietrzak, Goldstein, Southwick, & Grant, ; Seal et al, ). There are considerable data indicating that highly selective DA D 3 receptor antagonists are efficacious in decreasing the appetitive and reinforcing actions of cocaine, methamphetamine, nicotine, heroin and ethanol in rats (Heidbreder & Newman, ; Heidbreder et al, ; Sokoloff & Le Foll, ). Thus, if these results can be translated to humans, they suggest that highly selective DA D 3 receptor antagonists may be efficacious in attenuating PTSD symptoms, while simultaneously decreasing the likelihood of drug abuse and addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, bilateral microinjection of SB‐277011A into the NAc, but not into the dorsal striatum, significantly attenuates the stress‐induced reinstatement of cocaine–seeking behavior (Xi et al, ), implicating a specific locus of action in the brain. In addition, in vitro studies indicate that dopamine (DA) D 3 receptor mRNA is present in limbic brain regions (i.e., amygdala, mesencephalic DA neuron cell bodies) that modulate responses to stressful internal and environmental stimuli linked to anxiety and fear (Heidbreder et al, ; Sokoloff & Le Foll, ). In humans, D 3 receptor mRNA expression closely resembles that of seen in the rodent brain (Landwehrmeyer, Mengod, & Palacios, ; Suzuki, Hurd, Sokoloff, Schwartz, & Sedvall, ).…”
Section: Introductionmentioning
confidence: 99%
“…These neurons selectively express A 1 R and D 1 R (and D 3 R in the ventral striatum). [136][137][138] The striato-pallidal neurons of the indirect motor pathway, connects the striatum with the lateral segment of the globus pallidus and the ventral pallidum, and selectively expresses A 2A R and D 2 R.…”
Section: Striatal Adenosine Neurotransmissionmentioning
confidence: 99%
“…Stimulation of D1‐like receptors results in an activation of adenylate cyclase, while agonist stimulation of D2‐like receptors results in an inhibition of adenylyl cyclase activity, an increase in the release of arachidonic acid, and an increase in phosphatidylinositol hydrolysis . A great deal of experimental evidence suggests that there is a dysregulation of D2 and D3 receptors in a number of CNS disorders . For example, Positron Emission Tomography (PET) imaging studies in chronic cocaine abusers and autoradiography studies in rhesus monkeys having a chronic history of cocaine self‐administration have revealed a downregulation of D2‐like receptors, whereas an autoradiography study using a D3‐preferring agonist reported an upregulation of D3 receptors in human cocaine overdose victims when compared with age‐matched controls .…”
Section: Introductionmentioning
confidence: 99%